ANALISIS RASIO KEUANGAN SEBAGAI INDIKATOR MEMPREDIKSI KEBANGKRUTAN PADA BANK BRI TAHUN 2019-2021 - Aini, Nisrina Qurrotul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
Banking is a business entity that collects and distributes funds from the community and for the community. So to maintain the stability of money managed by banks, they must control their financial operations. One of them is by analyzing bankruptcy predictions. This study aims to predict bankruptcy in banks listed on the Indonesia Stock Exchange. The data used are financial reports from Bank Rakyat Indonesia, Tbk. The analytical method used is the altman Z-Score ratio analysis. The results of this study indicate that the Altman Z-Score ratio analysis is less than 1.1, meaning that Bank Rakyat Indonesia, Tbk is predicted to have a high probability of going bankrupt. It is advisable for Bank Rakyat Indonesia to make financial improvements in order to anticipate bankruptcy.